Traumatic Rupture of the Left Main Bronchus Case report & review of the literatures - Hussen, Waleed M. (Journal of the Faculty of Medicine Baghdad, 2011)
Rupture of the trachea or main bronchus can occurs during severe chest trauma and this event has been reported since more than a century. This is a report of a 19 year old male patient sustained car accident leading to loss of consciousness due to multiple trauma ,involving specially the head and the chest that he needs assisted ventilation in an intensive care unit and later a tracheostomy .The patient regain his consciousness gradually , and a late diagnosis of traumatic rupture of the left main bronchus , which was approved by bonchoscopy and CT chest .Surgical repair of the ruptured left main bronchus was accomplished sixty days from the admission with the lung fully expanded on a post operative chest X-ray . The patient referred later to the ENT Department , thereafter a successful weaning from the tracheostomy was performed .The patient discharged well , but he was in need for regular bronchoscopic dilatation for a tracheal stricture as a complication of tracheostomy .The patient is still well during the follow up period . The report will includes a review of the literatures about this relatively uncommon post traumatic condition.